The Effects of Product Differentiation and Brand Image on Customer Loyalty - Mauliano, Imellda Ricca; Arimbawa, Putu Adi Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – The increasingly competitive furniture industry demands that every business continuously innovate and build a strong brand image to maintain customer loyalty. Customer loyalty is a key factor in ensuring the sustainability and long-term growth of a business. This study aims to determine the effect of product differentiation and brand image on customer loyalty at Jati Indah Furniture. Design/methodology/approach – The research uses an explanatory research design, which seeks to explain causal relationships between the studied variables. The population of this study consists of customers who have purchased furniture or interior products from Jati Indah Furniture between January and July 2024. The sampling technique used is probability sampling with a simple random sampling method, involving a total of 60 respondents. Data were collected through an online questionnaire distributed via Google Forms, and the data analysis was conducted using Multiple Linear Regression with SPSS version 30. Findings – The results show that product differentiation has a positive and significant effect on customer loyalty. Similarly, brand image also has a positive and significant impact on customer loyalty at Jati Indah Furniture. These findings indicate that product differentiation strategies and strong brand image development are crucial in fostering customer loyalty. Originality/value – This study provides practical insights for furniture business owners to enhance competitiveness through product innovation and consistent brand positioning.